Comparing Powerpoint Experts' and University Students' Opinions about Powerpoint Presentations - MacKiewicz, Jo (Journal of Technical Writing and Communication, 2008)
Technical communication instructors want to help students, as well as professionals, design effective PowerPoint presentations. Toward this end, I compare the advice of academic and industry experts about effective PowerPoint presentation design to survey responses from university students about slide text, visual elements, animations, and other issues related to PowerPoint presentation design and delivery. Based on this comparison, I suggest some topics, such as PowerPoint's Slide Sorter view, that technical communication instructors and other presentation instructors might address when they cover presentations in their classes or seminars.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC90dy4zOC4yLmQ